A Management information system and a total system design of the Office of the Tanodbayan ng Pilipinas - Calugcug, Lou Nicholas; Manalo, Maricar; Paul, Jeremias Jr.; Reyes, Angela Haya.; Silvino, George; Taladua, George; Ungco, Edgardo; Villamor, Roy. (Diliman, Quezon City College of Engineering, 1982)
In coming up with the proposed systems design, for the Office of the Tanodbayan, making use of an efficient combination of men and materials, the project team constantly referred to the overall objective of the office which is "to give effect to the constitutional right of the people to petition the government for redress of grievances and to promote higher standards of integrity and efficiency in the government service". Hence the project team designed the system so as to maximize its services to the public and to the government as a whole, while taking into consideration its organizational and financial constraints. The Total System (in reference to the Office of the Tanodbayan) was subdivided into three major subsystems which are the Records Management Subsystem, the Evaluating Subsystem, and the Investigation and Prosecution Subsystem; two internal complimentary subsystems which are the Finance and Administrative Subsystems; a Management Information Subsystem consisting of the Management and Planning Subsystem (Monitoring Subsystem) and a Control Subsystem (Decision makers); and external complimentary subsystems such as the Fact-finding Agencies, the Sandigan bayan, and other coordinating agencies. This subdivision was made instead of following the organizational structure, for a more convenient view of the interrelationships within the system. Thus, we could properly set the functions of each subsystem according to the hierarchy of objectives. To assist the Management (Tanodbayan and other decision makers) in obtaining a clear-cut picture of the system in certain points in time, a Management Information has been developed. This Information System is primarily composed of reports, both oral and written, generated from even the smallest units (the personnel involved in each subsystem) and aggregately presented by the Management Information System is vital in aiding the Tanodbayan in decision making and making the proper recommendations to any government agency or official concerned. The highlights of our recommendations are: (1) the inclusion of measures of performance per subsystem for effective control, (2) the expansion of the investigating group so as to accommodate the referrals made by the Evaluation Subsystem for additional facts, (3) the centralization of the Records System and (4) the modification of the filing system of the Records Management Subsystem.
Feasibility study
Typescript
Submitted in partial fulfillment of the course requirements in IE 154 : Information Systems I
Keywords: Office of the Tanodbayan ng Pilipinas; Management information systems; Tanodbayan; Information resources management